2006
DOI: 10.1002/ejic.200501100
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Crystal Structure Analysis of the First Terdentate [C,N,S] Thiosemicarbazone Complex with a Six‐Membered Palladacycle: Influence of Steric Effects on Ring Size

Abstract: The reaction of the thiosemicarbazone ligands 1‐(COMe)‐3‐[C(H)=NN(H)C(=S)NHR]C8H5N, (R = H a, Me b, Et c) with potassium tetrachloropalladate in an ethanol/water mixture led to the new tetranuclear palladium(II) compounds [Pd{1‐(COMe)‐3‐[C(H)=NN=C(S)NHR]C8H4N‐k3C5,N,S}]4 (R = H 1a, Me 1b, Et 1c) which contain six‐membered metallacycles. The thiosemicarbazone ligands in these complexes are terdentate through the C, N, and S atoms and are deprotonated at the NH group. The Pd–S bond formed is sufficiently strong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Several structures of cyclometallated complexes derived from Schiff bases in which the ligand is coordinated through a CH 2 carbon have been described previously; however, with the exception of a recent example reported by us, [48] in the remaining cases the six-membered cyclo- Symmetry transformations used to generate equivalent atoms: metallated ring showed a nonplanar geometry with a boatlike structure. [16,18,[49][50][51][52][53] We believe that in 1c the tetranuclear structure brings close two of the cyclometallated ligands, thus imposing planarity of the ring in order to avoid mutual steric repulsion.…”
Section: Crystal Structure Of 1cmentioning
confidence: 93%
“…Several structures of cyclometallated complexes derived from Schiff bases in which the ligand is coordinated through a CH 2 carbon have been described previously; however, with the exception of a recent example reported by us, [48] in the remaining cases the six-membered cyclo- Symmetry transformations used to generate equivalent atoms: metallated ring showed a nonplanar geometry with a boatlike structure. [16,18,[49][50][51][52][53] We believe that in 1c the tetranuclear structure brings close two of the cyclometallated ligands, thus imposing planarity of the ring in order to avoid mutual steric repulsion.…”
Section: Crystal Structure Of 1cmentioning
confidence: 93%
“…The Pd(1)-C(1) bond [2.006(6) Å ] is shorter than the expected value of 2.081 Å probably due to partial multiple-bond character [21]. The Pd(1)-N(1) bond [2.015(5) Å ] is comparable with those reported for Pd(II) thiosemicarbazone complexes (sum of the covalent radii for palladium and nitrogen: 2.01 Å ) [22].…”
Section: Description Of the Crystal Structuresmentioning
confidence: 76%
“…Up to this point, our previous studies related to thiosemicarbazone palladacycles showed that treatment of the ligand with an appropriate palladium salt gave tetranuclear species, always with two perpendicular pairs of parallel metallated systems, set on a central Pd 4 S 4 eight‐membered ring . Where bonding of the metal to the phenyl carbon is absent and the metal remains linked only to the nitrogen and sulfur donors, the tetranuclear arrangement of the molecule is preserved .…”
Section: Thiosemicarbazone [Cns] Palladacycles and Bidentate [Ps] mentioning
confidence: 81%
“…[16] Up to this point, our previous studies related to thiosemicarbazonep alladacycles showedt hat treatment of the ligand with an appropriate palladium salt gave tetranuclears pecies, alwaysw ith two perpendicular pairs of parallel metallated systems, set on ac entral Pd 4 S 4 eight-membered ring. [13,18] Where bondingo ft he metal to the phenyl carbon is absent and the metal remains linked only to the nitrogen and sulfur donors, the tetranuclear arrangemento ft he molecule is preserved. [19] Therefore, our outlookf or the progress into further visible features related to the chemical behavior of these speciesw as to investigate alternative structuralc haracteristics originated by modifications in the architecture of the organic moiety and of its reaction pattern on treatment with the metal substrate;t he resultingt ailor-made route would then be the changes made in the central sulfur-palladium core.…”
Section: Thiosemicarbazone [Cns]palladacycles and Bidentate [Ps]mementioning
confidence: 99%